Does the sound radiation of ground significantly contribute to the sound emission of railway lines?. Issue 6 (2nd November 2021) - Villot, Michel; Jean, Philippe; Guigou-Carter, Catherine
ABSTRACT: The sound radiated by the ground vibration generated by trains has been estimated by calculation in a case study and compared to the total sound measured on-site. A 2.5D ground numerical model, calibrated from on-site vibration measurements, has been used to estimate the ground vibration field, from which the ground-borne sound radiated has been estimated using the Rayleigh Integral Method. According to the calculations, the estimated ground-borne sound radiated is dominant at low frequencies (below 125 Hz) and otherwise rather negligible compared to the sound directly emitted by the train/track system. Moreover, a small parametric study performed using a 2D source (vehicle and tracks) model coupled to the same ground model shows that the ground-borne sound radiated is ground dependent. The ground should be taken into account as a separate sound source when dealing with railway sound and should be added to the other known sources (track and vehicle components).